THE IDENTIFICATION OF BIOMARKERS TO PREDICT RESPONSE TO TREATMENTS IN ASTHMA - Lissa, Sutherland (2019)
Background: Asthma is a complex heterogeneous disease of the airways characterized by non-specific symptoms such as cough, wheeze and shortness of breath. Despite this known heterogeneity asthma patients are generally treated the same way. As such, patients are at risk of taking medications they either do not require or will not benefit from. The identification of biomarkers capable of aiding in disease phenotyping is essential to ensure patients receive treatments that will be of the most benefit to them.